Long‐term hepatitis E viral load kinetics in an immunocompromised patient treated with ribavirin. (5th March 2014) - Ambrosioni, J.; Mamin, A.; Hadengue, A.; Bernimoulin, M.; Samii, K.; Landelle, C.; Negro, F.; Kaiser, L.; Antonelli, G.
Abstract Hepatitis E virus (HEV) can cause chronic infections in immunocompromised hosts. Viral kinetics in plasma and stools are poorly understood, particularly during antiviral treatment. Prolonged faecal shedding may be a concern for transmission. We describe HEV kinetics in an immunocompromised patient with prolonged faecal shedding despite undetectable viraemia on ribavirin treatment.